(untitled) (Brazilian Journal of Police Sciences, 2023)
The paper studies the interoperability among intelligence agencies of the prosecutor office and the public security forces. It intends to stablish a compatibility between the control over the police activity that is performed by the prosecutor office, which can generate institutional antagonism, with the trustiness needed among the agencies and its actors involved in the intelligence. For this purpose, through bibliographic review, document analysis of the Brazilian legislation and case study, it examines the constitutional function of the prosecutor office and the control over the police. Then, it identifies the trustiness as a requirement for the cooperation in the intelligence among agencies. The study concludes that the Special Group of Organized Crime Combat and Intelligence Centers, headed by the prosecutor office, generates trustiness, which allows technical interoperability between those responsible for public safety.